Religion and Modernization in Southeast Asia (Book Review) - Hakim, Sudarnoto Abdul (Buletin Al-Turas, 1996)
the book which was written by Fred. R. Vonder Mehden, an Albert Thomas Professor of Political Science, at Rice University, Houston, is actually a result of efforts to understand the nature of th interrelationship of religion and modernization in Southeast Asia in the light of the theoritical assumptions presented by postwar social  scientists. It is no doubt that where as religions like Islam and Buddhism in countries such as Malaysia, Indonesia, and Thailand have acted both as inhibutors and agents of change, the social science literature spoke primarily to the negative role of rligion from the more possitive perspective. Mehden demonstrates the weakness of the theories developed by Social scientists in Western Europe and the U.S. without adequate field research and embodying major biases and misconceptionabout indigenous cultures and religions.